2017
DOI: 10.3389/fpls.2017.01132
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Cytological Studies on Mycosphaerella pinodes Infection of the Model Legume Medicago truncatula

Abstract: Ascochyta (Mycosphaerella) blight on cultivated peas is primarily caused by infection through asexual spores (pycnospores) of Mycosphaerella pinodes (Berk. et Blox.) Vestergren [recently renamed Peyronellaea pinodes (Berk. & A. Bloxam) Aveskamp, Gruyter & Verkley]. Using a model pathosystem involving Medicago truncatula and Mycosphaerella pinodes strain OMP-1, we examined the histology and ultrastructure of early infection events and fungal development including penetration by appressoria, vegetative growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Plant responses to pathogen infection involve a series of reactions associated with the reinforcement of cell walls, oxidative burst, the activation of the antioxidative system, hormonal adjustment, the synthesis of stress-related biomolecules (e.g., phytoalexins), and proteins related to both secondary [70] and primary metabolism [71], which are common to various fungal infections [72][73][74]. Up to now, the changes in the transcriptome and proteome of pea plants infected with D. pinodes or F. oxysporum have revealed an increase in the levels of various proteins, i.e., those involved in energy and amino acid metabolism, redox response, the synthesis of pisatin or pathogenesis-related (PR) proteins, and proteins involved in changes in the structures of the cell walls (e.g., lignin biosynthesis, the modification of the degree of methyl esterification of pectins) [2,28,[75][76][77][78][79]. However, data on the metabolic responses of pea to fungal infections are scarce.…”
Section: Changes In Polar Metabolic Profiles Of Pea Seedlings After I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant responses to pathogen infection involve a series of reactions associated with the reinforcement of cell walls, oxidative burst, the activation of the antioxidative system, hormonal adjustment, the synthesis of stress-related biomolecules (e.g., phytoalexins), and proteins related to both secondary [70] and primary metabolism [71], which are common to various fungal infections [72][73][74]. Up to now, the changes in the transcriptome and proteome of pea plants infected with D. pinodes or F. oxysporum have revealed an increase in the levels of various proteins, i.e., those involved in energy and amino acid metabolism, redox response, the synthesis of pisatin or pathogenesis-related (PR) proteins, and proteins involved in changes in the structures of the cell walls (e.g., lignin biosynthesis, the modification of the degree of methyl esterification of pectins) [2,28,[75][76][77][78][79]. However, data on the metabolic responses of pea to fungal infections are scarce.…”
Section: Changes In Polar Metabolic Profiles Of Pea Seedlings After I...mentioning
confidence: 99%
“…Comparative studies of cultivars more and less resistant to D. pinodes infection revealed common metabolomic responses such as increased contents of sugars (but not sucrose), sugar alcohols, and glycolysis/tricarboxylic acid (TCA) cycle intermediates and changes in amino acid content [87]. Moreover, it has been suggested that D. pinodes infection in pea plants is regulated by jasmonate (JA) and ethylene (ET) pathways [78,79] and can induce a hypersensitive response that leads to pathogen-induced cell death [28].…”
Section: Changes In Polar Metabolic Profiles Of Pea Seedlings After I...mentioning
confidence: 99%
“…This suggested the hyphae were aberrated, which could be a structural defence response (Suzuki et al, 2017). During the penetration process, the host cell wall became degraded and/or swollen near the infection hyphae.…”
Section: Stability Of Aggressiveness Traits Among Highly Aggressive Imentioning
confidence: 99%
“…Plant-pathogenic fungi commonly form infection structures to penetrate the host plant cell wall during the early stage of the infection process. For example, A. pinodes forms infection cushions to penetrate the leaves of peas and Medicago truncatula ( 3 , 16 ). Various carbohydrate-active enzymes (CAZymes) secreted by fungi to degrade plant cell walls are critical for penetration and virulence.…”
Section: Introductionmentioning
confidence: 99%